Increasing Social Inclusion through Social Guarantees : A Policy Note - World Bank (Washington, DC, 2013)
This policy note seeks to contribute to the consideration of social guarantees as tools for the design and/or monitoring of social policy and service delivery. It proposes a range of options to improve the delivery of and access to social services that can further social inclusion and democratic governance. The application of a social guarantee framework to social policy could significantly enhance the effectiveness of policy implementation in Latin America and the Caribbean, and can have a direct and positive impact on poor and vulnerable groups. This policy note is not intended as a blueprint for developing a social guarantee approach to social policy design and service delivery. Rather, it discusses the principles that could guide such undertaking, and it provides examples of how different countries have developed and implemented social programs using this approach. Social policy plays a critical role in promoting inclusion and strengthening democratic governance. As such, it contributes to the realization of normative human rights commitments. This document suggests that a social guarantee approach can be used to strengthen the delivery and monitoring of social programs. It highlights the importance of understanding and building upon the existing socio-political context of each country. This policy notes suggests that a system of social guarantees provides a way of addressing these concerns by enabling the state to provide: a) clarity of minimum standards, which can be revised on an ongoing basis; b) a framework for equity between those who receive services from different providers (public, private, voluntary); c) a framework for redress if minimum standards are not met; and d) a process for citizen participation in public and private provision.